Exogenous application of EE-GRSP and changes in citrus rhizosphere properties - WU, QIANG-SHENG; SRIVASTAVA, A K; WANG, SHUANG; ZENG, JIA-XIN (The Indian Journal of Agricultural Sciences, 2015)
Mycorrhization-induced secretion of glomalin-related soil protein (GRSP) is known to contribute in improving soil fertility and aggregate stability. But, there is hardly any evidence that exogenous GRSP could produce the similar type of response. The present study was, therefore, carried out to extract easily extractable GRSP (EE-GRSP) from citrus rhizosphere soils and evaluate the response at 1/4, 1/2 and full strength EE-GRSP solutions watered into the rhizosphere of 27-year-old Satsuma mandarin (Citrus unshiu) grafted on the rootstock of Poncirus trifoliata. After 5 months, exogenous EE-GRSP treatments produced significantly positive responses on endogenous EE-GRSP, difficultly-extractable GRSP (DE-GRSP), total GRSP production and soil organic carbon (SOC) content. A significantly positive correlation of these endogenous GRSP fractions with SOC indicated an active participation of GRSP on soil C pool. Exogenous GRSP showed a key role in binding water-stable aggregate (WSA) at 2–4, 1–2, 0.5–1, and 0.25– 0.5 mm size and enhancing WSA stability through changes in mean weight diameter (MWD). A stronger correlation of EE-GRSP and total GRSP with MWD was observed than DE-GRSP fraction. On the other hand, exogenous EEGRSP showed a positive effect on soil phosphatase activity, and soil endogenous EE-GRSP was significantly and positively correlated only with neutral phosphatase. Our studies suggest that exogenous EE-GRSP could be used as an effective regulator to affect soil fertility and soil structure within citrus rhizosphere.